MEMAHAMI KEBUTUHAN WISATAWAN MUSLIM DALAM BERWISATA - Yuli Arisanti (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Moslem people have certain needs when travel either for tourism or other purposes. Halal tourism grows fast internationally and the muslim traveler needs should be accommodated for those targeting muslim traveler. The purpose of this research is to gain better understanding about muslim consumer behavior and muslim traveler needs. Literature review and observation have been conducted to collect information, analyzed it and then written it. Muslim traveler needs prayer space facilities and halal food and beverages as the most priority. Hotel accommodation, public facilities, social environment which are muslim friendly are the next needs for muslim traveler. Application and technology are helpful and will make traveling more convenience. The recommendation for tourism and hospitality industry who targeting muslim traveler should improve and provide the needs and what become concern for muslim traveler. Thus tourism industry could satisfy muslim traveler and raise their visit.Keywords: Moslem Traveler; Consumer Behavior; Halal Tourism; Moslem Friendly Tourism